(Invited) Heteroepitaxy and Strain Engineering of Germanium-Silicon-Tin Ternary Alloy Semiconductor Thin Films for Energy Band Design. (8th September 2020) - Nakatsuka, Osamu; Shibayama, Shigehisa; Kurosawa, Masashi; Sakashita, Mitsuo
Abstract : Strain engineering of group-IV semiconductor thin film is a key for energy band design and engineering for electronic and optoelectronic applications. In this paper, we report our recent achievements for strain relaxation method of Ge1 − x − y Si x Sn y ternary alloy semiconductor epitaxial layer on various substrates. Virtual Ge substrate effectively enhances the strain relaxation of Ge1 − x − y Si x Sn y layer and also improves the surface morphology and uniformity after the strain relaxation. Ion implantation into Ge substrate is also effective to enhance the strain relaxation and achieves a large in-plane lattice constant as a buffer layer for the growth of strain-relaxed Ge1 − x Sn x epitaxial layer with a Sn content as high as 10%.